Issues With Implementing Teaching Materials from A Standardised Professional Development Programme: Perspectives Among ESL Teachers - Wendy Hiew; Jill Murray (Penerbit UMS, 2023)
This study investigates the issues experienced by ESL teacher participants in implementing materials and activities from the Professional Up-skilling of English Language Teachers (ProELT) programme in their language classrooms. A review of past studies indicated limited research on large-scale, standardised professional development programmes involving English language teachers from primary and secondary schools (heterogeneous teaching levels) and urban and rural areas (heterogeneous districts) participating in the same programme. Hence, this study aims to fill this research gap by adopting a mixed methods explanatory sequential design utilising interviews, focus groups, a questionnaire survey and the ProELT coursebook. The findings reveal more than half of the modules in each section of the coursebook do not complement the Malaysia curriculum specifications for primary and secondary schools; this triangulates with the interview findings that most of the teachers found it challenging to adopt the ProELT teaching materials and activities in their lessons due to the lack of relevance of the course materials with their teaching curriculum and target students. In addition, findings from the questionnaire further substantiate the teachers’ suggestions that the ProELT content should complement the English language curriculum syllabus. The findings of this study have implications for the programme providers and the programme designers in designing future development programmes that cater to the teachers’ needs, personalising separate primary and secondary-level programme contents, and focusing on pedagogical content knowledge and subject matter vis-a-vis generic learning.